smartEducation: Developing Stress Management and Resiliency Techniques (LEARNing Landscapes, 2017)
smartEducation (Stress Management and Resiliency Techniques) is a mindfulness-based professional learning initiative positioned in a Faculty of Education of a Western Canadian university. Following similar evidence-based initiatives of mindfulness in education, the smartEducation curriculum comprises nine sessions offered in a variety of face-to-face, intensive, and blended formats. This renewal program supports the development of self-care techniques to cultivate personal and professional resilience through a greater understanding and control of breath, movement, and the physiology of emotions. The 20-hour program consists of eight two-hour sessions and a four-hour silent retreat. This article provides an overview of the research supporting mindfulness in education and presents the results of a pilot study conducted with preservice teachers enrolled in the smartEducation course.
Keywords: smartEducation (Stress Management and Resiliency Techniques); mindfulness; education; self-care; resilience; pre-service teacher